An Overview the Levels of Depression, Anxiety and Stress in Pharmacy Students Post Covid-19 Pandemic - dhanang prawira nugraha; Rodhi Anshari (Jurnal Ilmiah STIKES Yarsi Mataram, 2025)
Depression, anxiety and stress are psychological disorders that affect mental conditions. these conditions in students can cause a decrease in learning performance and can ultimately affect the cumulative grade point average. With Covid-19 under control, there has been a change in the learning system, which during the Covid-19 pandemic was carried out online has changed to offline again. This certainly affects the psychological condition of students. This study aimed to reveal the description of the levels of depression, anxiety, and stress after engaging in offline learning. This research was conducted with a cross-sectional design, the subjects of this study were all students of the pharmacy department who met the inclusion and exclusion criteria and the variables used in this study were gender, semester and levels of depression, anxiety and stress. The instrument used in this study was the Indonesian DASS-42 questionnaire and the analysis used in this study was descriptive analysis. The result is that female students experience the most severe levels of depression, anxiety and stress. whereas based on the semester students with very severe depression were most in the 3rd semester group, very severe anxiety was mostly experienced by students in 5th semester and very severe stress was experienced by students in 7th semester. The conclusion of this study showed that pharmacy students had a moderate level of depression, for anxiety levels and stress are at normal levels. ABSTRAK Depresi, kecemasan dan stress merupakan gangguan psikologis yang mempengaruhi kondisi mental. kondisi tersebut dapat menyebabkan penurunan prestasi belajar dan pada akhirnya dapat mempengaruhi indeks prestasi kumulatif. Dengan terkendalinya Covid-19, maka terjadi perubahan sistem pembelajaran yang selama pandemi Covid-19 dilakukan secara daring berubah menjadi luring kembali. Hal ini tentu berpengaruh pada kondisi psikologis mahasiswa. Penelitian ini ingin mengungkap bagaimana gambaran tingkat depresi, kecemasan dan stres setelah melakukan pembelajaran secara luring. Penelitian ini dilakukan dengan desain cross sectional, subjek penelitian ini adalah seluruh mahasiswa jurusan farmasi yang memenuhi kriteria inklusi dan eksklusi dan variabel yang digunakan dalam penelitian ini adalah jenis kelamin, semester dan tingkat depresi, kecemasan dan stres. Instrumen yang digunakan dalam penelitian ini adalah kuesioner DASS-42 Indonesia dan analisis yang digunakan dalam penelitian ini adalah analisis deskriptif. Hasil penelitian menunjukkan bahwa mahasiswa perempuan mengalami tingkat depresi, kecemasan dan stres yang paling berat. Sedangkan berdasarkan semester mahasiswa dengan depresi sangat berat paling banyak terdapat pada kelompok semester 3, kecemasan sangat berat paling banyak dialami oleh mahasiswa semester 5 dan stres sangat berat paling banyak dialami oleh mahasiswa semester 7. Kesimpulan dari penelitian ini menunjukkan bahwa mahasiswa farmasi memiliki tingkat depresi yang sedang, untuk tingkat kecemasan dan stres berada pada tingkat normal